Geoquímica e geocronologia (U-Pb e Lu-Hf) da Suíte Intrusiva Alvorada, SW do Cráton Amazônico : magmatismo tardio relacionado à Orogenia Cachoeirinha - Franco, Luiz Claudio Durão (2019)
The rocks of the Alvorada Intrusive Suite are located along an wide and narrow belt in the SW region of the state of Mato Grosso. They are granitioritic to syenogranitic rocks, isotropic to slightly foliated, of fine to medium granulation, light gray to pink in color, with hypdiomorphic and sometimes porphyritic equigranular texture, sometimes porphyritic, composed of quartz, alkaline feldspar, plagioclase, biotite, hornblende and, as accessory minerals titanite, allanite, apatite, monazite and zircon. It has two facies, syenogranitic and monzogranitic with a predominance of monzogranites. The magmatism that originated the Alvorada Intrusive Suite rocks is classified as sub-alkaline, high-potassium calcium-alkaline type, having a metaluminous to peraluminous character, representing type I granitoids in a magmatic arc environment. Zircon geochronological analyzes performed by the U-Pb LAICP-MS method show that these rocks crystallized at 1575 ± 16. Lu-Hf analyzes performed on the same zircons reveal model ages between 1.59 and 1.79Ba, with positive εHf with positive values between + 5.4 and + 10.6. This age represents a new frontier of the geological knowledge of the Cachoeirinha Orogen. The data presented suggest that the rocks of the Alvorada Intrusive Suite were generated in a magmatic arc environment during the Cachoeirinha Orogeny of Calimian age, portraying the final phase of an important accretion event.